2012
DOI: 10.1007/s00181-012-0579-z
|View full text |Cite
|
Sign up to set email alerts
|

Firm growth in multinational corporate groups

Abstract: This paper formulates an econometric firm growth model that explicitly accounts for the interdependence of firm performance within corporate networks and is in line with several economic theories on firm growth. We estimate the model for national and multinational corporate groups (MNEs) using a recently introduced instrumental variable estimation procedure for peer group effects developed by Lee (2007). In our data for corporate groups the observation of fast growing young firms and slow growing old firms dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…While peer-effects econometrics has been applied many times to analysis of neighborhood effects, substance use among teenagers, and peer group effects among university room-mates (see Soetevent (2006) for a survey), it has recently been applied in the context of firm growth. Oberhofer and Pfaffermayr (2010) investigate the growth of multinational groups, and observe positive externalities within vertically organized multinational networks, although horizontally organized networks display negative growth spillovers.…”
Section: Peer-effects Econometricsmentioning
confidence: 99%
See 2 more Smart Citations
“…While peer-effects econometrics has been applied many times to analysis of neighborhood effects, substance use among teenagers, and peer group effects among university room-mates (see Soetevent (2006) for a survey), it has recently been applied in the context of firm growth. Oberhofer and Pfaffermayr (2010) investigate the growth of multinational groups, and observe positive externalities within vertically organized multinational networks, although horizontally organized networks display negative growth spillovers.…”
Section: Peer-effects Econometricsmentioning
confidence: 99%
“…We follow the methodology used in Oberhofer and Pfaffermayr (2010) Consider the following regression equation:…”
Section: Peer-effects Econometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach relates our paper to a recent literature on the organization of production along the value chain (e.g., Antràs and Chor 2013;Costinot et al 2013), because using weights on input-output dependence allows us to draw conclusions about the relative position (upstream or downstream) of entities (and countries) in the global value chain. Moreover, the approach is related to the literature unveiling vertical international linkages in the productivity (see Bernstein and Mohnen 1997;Keller 2002;Morrison Paul and Siegel 1999;Smarzynska Javorcik 2004), growth and volatility (Burstein et al 2008;Kleinert et al 2012;Oberhofer and Pfaffermayr 2013), and, hence, the profitability across units (firms, sectors, and even countries). Comparing input-output-related interdependencies of affiliates' investments to geographic-distance-related interdependencies also permits drawing conclusions about the relative importance of different channels of interdependence.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that spatial spillovers matter between plants located in the same city. A recent study by Oberhofer and Pfaffermayr (2013) investigated firm growth from the network perspective. They used the IV-estimation procedure for peer group effects and European firm level data to explicitly incorporate independence within multinational corporate groups.…”
mentioning
confidence: 99%